Identifying Measures to Promote Teachers’ Job Satisfaction in Public Secondary School - Adeoye, Moses Adeleke (Bumi Publikasi Nusantara, 2023)
An understanding of teachers’ job satisfaction is needed to provide overall and different dimensions of job satisfaction and the effects of individual factors. The overall attitude and views of teachers toward their working conditions and profession affect teaching and the quality of the school. Research on measures to promote teachers’ job satisfaction in public secondary schools can help us understand teachers’ overall and particular aspects of job satisfaction and provide scientific grounds for resolving problems. The factors affecting job satisfaction determine the dimensions and constituents of teachers’ job satisfaction. Conducive working conditions, promotional opportunities, fair remuneration, and teacher empowerment were found to be the major factors affecting the job satisfaction of teachers. This paper reveals that most of the factors related to motivation and hygiene factors in Herzberg's Two-factor theory are influential on teachers' job satisfaction. Concepts related to teachers' job satisfaction and factors affecting job satisfaction were discussed.